Coronary Artery Disease New Approaches without Traditional Revascularization - Barsness, Gregory W.; Holmes, David R.; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2012)
While the majority of patients with symptomatic coronary artery disease (CAD) achieve acceptable angina relief through medical therapy, coronary artery bypass grafting and percutaneous coronary intervention, a growing number are not candidates for these procedures.  Standard procedures are largely palliative, and symptom recurrence is relatively common, while the increase in obesity and type 2 diabetes may result in a potential explosion in severe, diffuse CAD.  As these trends continue, the population of patients who fail to achieve adequate symptomatic improvement through standard medical and revascularization strategies will grow exponentially. Therapeutic options for these patients are currently limited, but experimental and developing strategies are appearing, including transmyocardial laser revascularization, therapeutic angiogenesis, spinal cord stimulation, external counterpulsation, various novel medical therapies and complex percutaneous and surgical revascularization strategies. Coronary Artery Disease: New Approaches without Traditional Revascularization is a comprehensive and clinically oriented review of the epidemiology and basic science foundation for studies in this challenging group of patients. Current and novel treatment strategies are put in the context of past failures and future directions, and the Editors and their carefully chosen group of contributors provide a fascinating insight into the direction and focus for clinical practice and research in this area. As such this book is an important reference not only for clinical cardiologists, cardiac surgeons and interventionalists but also researchers into novel diagnostic measures, new surgical techniques and other treatment regiments in CAD.
Epidemiology of Cardiovascular Disease and Refractory Angina -- Basic Science Concepts -- Natural History in Humans -- Therapeutic Goals in Patients with Refractory Angina -- Medical Therapy for Chronic Refractory Angina -- External Counterpulsation -- Transmyocardial Laser Revascularization -- Invasive and Device Management of Refractory Angina -- Cardiac Transplantation for Ischemic Heart Disease -- Alternative Therapies for Chronic Refractory Coronary Artery Disease -- Nonspecific Placebo Effects -- Prognostic Implication of Depression in Ischemic Syndromes.
Keywords: Cardiology; Cardiology